2019
DOI: 10.1186/s12969-019-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

Disease course and treatment effects of a JAK inhibitor in a patient with CANDLE syndrome

Abstract: Background CANDLE syndrome (an acronym for Chronic Atypical Neutrophilic Dermatosis with Lipodystrophy and Elevated Temperature) is a recently described rare autosomal recessive disorder charaterized by systemic autoinflammation. Clinical manifestations include presentation in the first year of life, episodes of fever accompanied by erythematous skin lesions, progressive lipodystrophy, violaceous periorbital swelling and failure to thrive. This syndrome is caused by loss of function mutations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 25 publications
0
30
0
2
Order By: Relevance
“…Several case studies have reported improvement of AA in patients who received JAK inhibitors for other autoimmune/autoinflammatory disorders or JAK-STAT gain-of-function mutation diseases (99103).…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Several case studies have reported improvement of AA in patients who received JAK inhibitors for other autoimmune/autoinflammatory disorders or JAK-STAT gain-of-function mutation diseases (99103).…”
Section: Alopecia Areatamentioning
confidence: 99%
“…Immunosuppressants, as well as targeted antibody therapies including anti‐TNFα antibodies, IL‐1Ra (anakinra), IL‐6Ra (tocilizumab) could not show sufficient effect. In contrast, the use of JAK inhibitors seems to be promising, as been reported in case reports [99].…”
Section: Proteasome‐associated Auto‐inflammatory Syndromes (Praas) (Mmentioning
confidence: 99%
“…G-CSFR signals through Jak2 suggesting a possible role of Jak2 creating cytokine dysregulation. In addition, increased expression of IFNγ was also described in patients and rare genetic autoinflammatory diseases characterized by high IFNγ production also represent neutrophilic dermatosis where Jak inhibitor therapy significantly improved symptoms in some cases (224).…”
Section: Tyrosine Kinases In Inflammatory Skin Diseasesmentioning
confidence: 99%